The long history of prevention: Social Defence, security and anticipating future crimes in the era of ‘penal welfarism’ - Heath-Kelly, Charlotte (Theoretical criminology, 2022)
Using a combination of documentary and archival research methods, this article explores the development of Social Defence criminology across the 19th and 20th centuries—highlighting the influence the ‘new’ Social Defence movement had upon the United Nations' and Council of Europe's international crime policy programmes. By exploring the integration of Social Defence within these international programmes, the article is able to challenge several longstanding arguments in Criminology which associate pre-crime and the securitization of criminal justice with the neoliberal era. Social Defence scholars influenced International Organizations to research and disseminate anticipatory mechanisms to identify and reform potential deviants decades earlier than prominent theses suggest. These measures were steeped in the language of security and were oriented towards the prevention of future juvenile crime. The article argues for a reweighing of the influence of Social Defence criminology and against accounts which draw significant divisions between ‘penal welfarism’ and ‘neoliberal penality’.